The use of virtual reality as a perspective-taking manipulation to improve self-awareness in Alzheimer’s disease - Latgé-Tovar, Sofia; Bertrand, Elodie; Piolino, Pascale; Mograbi, Daniel C. (Frontiers in Aging Neuroscience, 2024)
Lack of awareness of symptoms or having a condition referred to as anosognosia is a common feature of individuals with Alzheimer’s Disease (AD). Previous literature on AD reported difficulties in evaluating self-abilities, often showing underestimation of limitations. There is increasing evidence that the perspective through which information is presented may moderate the performance appraisal and that anosognosia in AD might be a consequence of a deficit in assuming a third-person perspective. In this context, some studies showed that subjects may better recognize self-and other-difficulties when exposed to a third-person perspective. Considering the variety of approaches aiming to investigate the lack of awareness, there is still a scarcity of methods that provide great ecological validity and consider more than one facet of awareness, thus failing to offer more accurate evaluations of daily experiences. The present paper primarily addresses the theme of the multidimensional character of awareness of abilities in AD and the effect of perspective-taking on its trajectories. The focus turns to virtual reality as a promising tool for a greater evaluation of perspective-taking and self-awareness. Particularly, these systems offer the possibility to involve users in cognitive and sensorimotor tasks that simulate daily life conditions within immersive and realistic environments, and a great sense of embodiment. We propose that virtual reality might allow a great level of complexity, veracity, and safety that is needed for individuals with AD to behave according to their actual abilities and enable to explore the liaison between the subject’s viewpoint, performance, and self-evaluation. In addition, we suggest promising clinical implications of virtual reality-based methods for individualized assessments, investigating specific impacts on subjects’ life and possible improvements in their awareness.